PENGUKURAN KINERJA RANTAI PASOK MENGGUNAKAN SUPPLY CHAIN OPERATIONS REFERENCE (SCOR) DI UD. ANANDA - Iphov Kumala Sriwana; Nurul Hijrah S; Arief Suwandi; Roesfiansjah Rasjidin (Fakultas teknik Universitas Muhammadiyah Jakarta, 2021)
Supply chain performance measurement has an important role to play in formulating a strategy in running a company's business. UD Ananda is a company engaged in the production and sale of wooden furniture. UD. Ananda has never done a performance measurement in the supply chain that runs at the company. The purpose of this study is to determine the performance value and achievement of each company performance indicator. Performance measurement using the Supply Chain Operations Reference (SCOR) model. This model includes a performance indicator / Key Performance Indicator (KPI) that has been validated using a questionnaire to then determine the weight of each performance indicator point using the Analytical Hierarchy Process (AHP) and normalizing the score with Snorm De Boer. The traffic light system method is used to display performance indicators that are far from the company's target and become a priority for improvement, namely 7 indicators out of 17 validated indicators. The results of supply chain performance measurement at UD. Ananda was 71.43 for June and 79.37 for July. This value indicates that the supply chain performance value in the company is in a position of good performance.